Clinical report of delayed recovery after general anaesthesia in elderly patients with cervical spine surgery: A case report. Issue 10 (October 2022) - Liu, Yang; Huang, Huilian
This report describes a case of a 70-year-old male that underwent decompression laminectomy and internal fixation under general anaesthesia. After extubation, the patient gradually developed no response to instructions and the disturbance of consciousness persisted with unequal pupils in size, but clinical neurological findings and a brain computed tomography scan showed no organic abnormalities. A careful medical history undertaken by anaesthesiologists revealed that the patient had a history of trauma to his left eye, resulting in blindness in this eye, but the surgeons, anaesthesiologists and nurses did not find these problems before the operation. The diagnosis in this case was prolonged unconsciousness due to delayed recovery from anaesthesia. Careful titration of the dose based on individual response in order to reduce adverse effects of general anaesthetics is especially important in elderly patients. Multiple checks of the patient information, surgical safety checklist and medical history by anaesthesiologists, surgeons and nurses can minimize the chance of an adverse outcome.